PTU-064 Pre-liver transplant biopsy in hepatocellular carcinoma: a potential exclusion criterion for transplantation?. (28th May 2012) - Young, R; Aldiwani, M; Hakeem, A; Nair, A; Wyatt, J; Toogood, G; Lodge, P; Jones, R; Prasad, R
Abstract : Introduction: In cirrhotic patients with hepatocellular carcinoma (HCC) pre-liver transplant (LT) staging biopsy of the largest tumour is undertaken in some centres. Proponents advocate that poor differentiation confers such poor prognostic significance that it can be used as an exclusion criterion for LT, resigning patients to palliative treatments. We do not carry out staging biopsies and sought to interrogate its potential use and impact on our practice in the context of ever increasing demands for organs. Methods: 65 consecutive patients undergoing orthotopic LT for radiologically diagnosed HCC at St James's University Hospital between 2006 and 2011 were identified for analysis from a prospectively maintained database. All patients had cirrhosis and incidental tumours were excluded. Diagnosis was in accordance to published guidelines and various clinic-pathological parameters were recorded. MRI findings were correlated with explant histological examination. Median follow-up was 24 months. Student t test, Mann–Whitney U test or related samples Wilcoxon Signed Rank tests were used where appropriate. The Kaplan–Meier method was used to determine survival with Log-Rank and Cox stepwise regression for survival comparisons. p<0.05 was considered to be statistically significant. Results: 3 year survival was 81% with the only independent predictor microvascular invasion (p=0.019). In 5 (7.7%) patients there was no HCC in the explant. A discrepancy between the definition of the largest lesion on pre-LT radiology and the largest explant tumour occurred in 5 (7.7%) cases. Tumours were classified as well, moderately or poorly differentiated in 39 (30.2%), 66 (51.2%) and 24 (18.6%) cases. In patients with multifocal HCC, 9 (34.6%) had tumours of differing grades. In two (7.7%) patients the largest tumour was well differentiated while smaller tumours in the explant were poorly differentiated. In one patient the largest lesion was benign with other smaller invasive carcinomas confirmed histologically. Conclusion: There is a need to optimise LT selection strategies for HCC. Microvascular invasion was the only independent predictor of outcome and the challenge of predicting it pre-operatively remains. Crucially, the largest lesion was not always representative of overall tumour burden or biological aggression and its potential use to exclude patients from curative treatment is questionable. Competing interests: None declared.